2008
DOI: 10.1007/s11269-008-9308-y
|View full text |Cite
|
Sign up to set email alerts
|

Water Pricing for Agricultural Production in the South of Iran

Abstract: Appropriate water resource allocation in dry land area is very important for farm management. Although very few systems for water distribution have efficient pricing, water resources should be allocated so that the marginal cost equals the marginal value product of water for all uses and users. When the marginal values are not equal, it is always possible to find a reallocation of water that increases net social benefits. Microeconomic techniques used for estimating the value of water and determining farmers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…They suggested that valuation of water should be a used to support the WFD implementation. Speelman et al (2009) assessed irrigation water values at small-scale irrigation schemes in South Africa and Esmaeili and Vazirzadeh (2009) utilized the same technique to irrigation in Iran.…”
Section: Methods To Assess the Value Of Irrigation Watermentioning
confidence: 99%
“…They suggested that valuation of water should be a used to support the WFD implementation. Speelman et al (2009) assessed irrigation water values at small-scale irrigation schemes in South Africa and Esmaeili and Vazirzadeh (2009) utilized the same technique to irrigation in Iran.…”
Section: Methods To Assess the Value Of Irrigation Watermentioning
confidence: 99%
“…There are many studies that include estimations of irrigation demand or water policies in this sector, including, in Spain, studies by Amador et al (1998), Berbel and Rodriguez (1998), Gómez-Limón and Riesgo (2004), Riesgo and Gómez-Limón (2005), Gómez-Limón and Martínez (2006), and Berbel and Mesa (2007), among others. At a European level, those published by Bazzani et al (2004), Manos et al (2007), , Latinopoulos (2008), and Esmaeli and Vazirzadeh (2009) are also relevant.…”
Section: Introductionmentioning
confidence: 91%
“…They further argued that the valuation of irrigation water will help in implementing the WFD. Speelman et al [37] and Esmaeili and Vazirzadeh [38] applied the RVM technique for the valuation of irrigation water in South Africa and Iran, respectively.…”
Section: Introductionmentioning
confidence: 99%